129k views
1 vote
HELP ASAP PLEASEE!! Simplify the sum or difference: 4√2-7√

a.) -√6
b.) -3√2
c.) -11√2
d.) 11√2
simplify the sum or difference: 3√7- √63
a.) -2√7
b.) -6√7
c.) -4√3
d.) 0

User Mansuro
by
6.3k points

2 Answers

3 votes


4√(2) - 7 √(2) = - 3 √(2)
First question answer is B.

3 √(7) - √(63) = √(63) - √(63) = 0
Second question answer is D.

3^2 = 9, 7 x 9 =63
**In case you're wondering why 3 square root 7 equals to square root 63.

Hope this helps.
User Yussan
by
6.4k points
1 vote

Answer:

1. Option b is correct,
-3√(2)

2. option d is correct; 0

Explanation:

1. Simplify the sum or difference:


4√(2) - 7√(2)

then, the result we get;


-3√(2)

Therefore, the difference of
4√(2) - 7√(2) is,
-3√(2)

2.

Simplify the sum or difference:


3√(7) - √(63)

We can write
√(63) as:


√(63) = √(9 \cdot 7) = √(3^2 \cdot 7) =3√(7)

then;


3√(7) -√(63) = 3√(7)-3√(7) = 0

Therefore, the difference of
3√(7) - √(63) is, 0

User Sasharz
by
6.0k points